Precarity and Flexibility in Platformised Tourism Work: A Scoping Review - Muhammad Fadhli Ramadhan; Tiffany Chairunnisa Ramadhania (Journal of Tourism, Hospitality and Travel Management, 2025)
The rapid proliferation of digital labour platforms has fundamentally restructured the global tourism and hospitality labor markets, ushering in a phenomenon widely termed the "gigification" of work. This transformation presents a central paradox: while platforms offer unprecedented temporal flexibility and low entry barriers for workers, they simultaneously institutionalize systemic vulnerabilities through algorithmic management and the erosion of traditional social protections. This scoping review aims to systematically map the scholarly literature published between 2020 and 2025 regarding the gig economy's impact on tourism and hospitality employment, identifying prevailing trends, platform typologies, and key thematic clusters of labor impact. In accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines, a systematic search was conducted in the Scopus database. The search strategy focused on the intersection of the gig economy, tourism/hospitality sectors, and labor dynamics. After a rigorous multi-stage filtration process, 165 open-access peer-reviewed articles were selected for qualitative synthesis and data charting. The findings indicate a significant upward trajectory in publications post-2023, with a geographical concentration in the Global North, although research in the Asia-Pacific region is rapidly expanding due to the rise of "super-apps." The review identifies four primary platform typologies: peer-to-peer accommodation, on-demand food delivery, tourism mobility, and specialized digital gigs. Synthesis of the evidence reveals a "flexibility-precarity nexus," in which the professionalization (or "hotelisation") of casual hosting and algorithmic control in delivery services has widened a "job quality gap," particularly for marginalized and migrant workforces. This study concludes that the gig economy is not merely a supplementary market but a structural force driving the downward pressure on employment standards across the broader hospitality ecosystem. The proposed conceptual framework highlights the need for future research into the long-term career trajectories of gig workers and the development of portable social benefits to mitigate algorithmic precarity in a post-pandemic tourism landscape.